Answer:
a.$375
Step-by-step explanation:
In order to calculate this you just have to keep in mind the amount of months that they paid in advance in the payment, so they had 2 months of rent fully paid in advance, we will represent that with "x", so we have 2x as the number of months, and it doesn´t say that they are paying unequal amounts of money so we will assume that they are paying half each of everything, so the equation will look like this:
If total payment= $1050 each, that means that for the two of them it´d be $2100, now we know that they paid 2 months plus a security deposit of $600, we just have to clear the payment to discover how much does the rent a month cost:
So one month of rent costs $750, if you divide that by 2, you get that Pat´s share of rent a month is $375.
Answer:
A
Step-by-step explanation:
4 in.
actual width:
18 ft
actual length: 16 ft
The plan width is
in.
Answer:
4.5 inches
Step-by-step explanation:
Given: plan length = 4 inches, actual width = 18 feet, actual length = 16 feet
To find: plan width
Solution:
1 feet = 12 inches
Plan length = 4 inches
Actual width = 18 feet= 18× 12 = 216 inches
Actual length = 16 feet = 16× 12 = 192 inches
Plan length/plan width = actual length/actual width
Answer:For 9n^3: (9n^3) * (-8n^2+9)
For -9n^3: (-9n^3) * (8n^2-9)
Step-by-step explanation:
The GCF is the greatest common factor.
The great common factor between 72 and 81 is 9 as 72=9*8 and 81=9*9
the GCF between n^5 and n^3=n^3.
SO the GCF is 9n^3.
But I would like to keep that leading coefficient positive, so i will factor -9n^3. It doesn't matter which one you choose, ill do both so u will have both ready.
For 9n^3: (9n^3) * (-8n^2+9)
For -9n^3: (-9n^3) * (8n^2-9)
(1,2), (-3,2)
Answer: $13.11
Step-by-step explanation:
hope this helps!
Answer:
P x 87 + 67 x 87 + (33 - P) x 87=8700
Step-by-step explanation:
explanation in pdf
The graph of f(x) = 3x is reflected across the x-axis is g(x) = f(-x) = 3x.
A graph can be defined as a pictorial representation or a diagram that represents data or values.
Reflection across the x-axis is defined as reflecting a point across the x-coordinate and y-coordinate change places, and When we have a point (x, y) and we reflect it over the x-axis, the result of the reflection is the point (x, -y)
To determine the graph of f(x) = 3x is reflected across the x-axis.
So the graph of f(x) = 3x is reflected across the x-axis.
⇒ g(x) = f(-x) = 3x
Hence, the graph of f(x) = 3x is reflected across the x-axis is g(x) = f(-x) = 3x.
Learn more about the graphs here:
#SPJ2
Answer:
g(x) = -f(x)
Step-by-step explanation:
When we have a point (x, y) and we reflect it over the x-axis, the result of the reflection is the point (x, -y)